Developing A Preventive Cost Control Model By Utilising Early Warnings And Risks - Bahaudin, Ahmad Yusni (2011)
The study of project control (cost control in particular) has only received limited attention in the Malaysian construction industry. The conventional project control system is basically corrective based, where project problems may have already occurred and the company may have experienced losses. An effective project control system must be able to anticipate emerging or unforeseeable problems, a deviation from the classical project methods which are often slow where problems may already exist. Early warnings can be included as part of the project risk management theories because “problem” and “risk” are apparently related to each other. The aim of this study is to develop a preventive cost control model that can be adopted by contractors to prevent or reduce unnecessary cost overruns.